Mechanisms of Neurodegeneration in Multiple Sclerosis - Eliseeva, D. D.; Zakharova, M. N. (Neuroscience and behavioral physiology, 2023)
Multiple sclerosis (MS) is a chronic inflammatory disease of the central nervous system (CNS), which leads to the formation of foci of primary demyelination in the white and gray matter and diffuse damage to axons and neurons. Despite significant progress in the development of drugs for relapsing-remitting MS, the impact on the progression of the disease remains insufficient. Diffuse and compartmentalized lymphocyte and macrophage infiltration of CNS tissue inhibits the differentiation of myelinating mature oligodendrocytes and disrupts remyelination processes. Chronic inflammation, which occurs when the blood–brain barrier (BBB) is intact, activates microglia, increasing axon and neuron damage and, as a result, triggers chronic oxidative stress and histotoxic hypoxia. It is currently important to clarify the mechanisms underlying neurodegeneration, which in the later stages of MS is caused by chronic neuroaxonal damage and impairment of regenerative capabilities and which largely determines disease outcome.